Five Newly Collected Turnip Mosaic Virus (TuMV) Isolates from Jeju Island, Korea are Closely Related to Previously Reported Korean TuMV Isolates but Show Distinctive Symptom Development - Hu, Wen-Xing; Kim, Byoung-Jo; Kwak, Younghwan; Seo, Eun-Young; Kim, Jung-Kyu; Han, Jae-Yeong; Kim, Ik-Hyun; Lim, Yong Pyo; Cho, In-Sook; Domier, Leslie L; Hammond, John; Lim, Hyoun-Sub (The plant pathology journal, 2019)
For several years, temperatures in the Korean peninsula have gradually increased due to climate change, resulting in a changing environment for growth of crops and vegetables. An associated consequence is that emerging species of insect vector have caused increased viral transmission. In Jeju Island, Korea, occurrences of viral disease have increased. Here, we report characterization of five newly collected turnip mosaic virus (TuMV) isolates named KBJ1, KBJ2, KBJ3, KBJ4 and KBJ5 from a survey on Jeju Island in 2017. Full-length cDNAs of each isolate were cloned into the pJY vector downstream of cauliflower mosaic virus 35S and bacteriophage T7 RNA polymerase promoters. Their fulllength sequences share 98.9-99.9% nucleotide sequence identity and were most closely related to previously reported Korean TuMV isolates. All isolates belonged to the BR group and infected both Chinese cabbage and radish. Four isolates induced very mild symptoms in but KBJ5 induced a hypersensitive response. Symptom differences may result from three amino acid differences uniquely present in KBJ5; Gly(382)Asp, Ile(891)Val, and Lys(2522)Glu in P1, P3, and NIb, respectively.